Supply chain resilience initiatives and strategies: A systematic review. (August 2022) - Rahman, Towfique; Paul, Sanjoy Kumar; Shukla, Nagesh; Agarwal, Renu; Taghikhah, Firouzeh
Highlights: We conduct a systematic review on supply chain resilience strategies. We analyze methodological, theoretical, and contextual justifications. We synthesize the content and examine knowledge gaps. We develop research questions and offer future research directions. Abstract: Supply chain resilience (SCRES) is an emerging research area, which plays a crucial role in protecting supply chains (SCs) against small- to large-scale disruptions. Over the past few years, many researchers have focused on developing SCRES strategies that have significantly contributed to mitigating SC disruptions. While the number of papers on this subject has been gradually increasing, the absence of a systematic literature review means that it is unclear which SCRES strategies for mitigating SC disruptions have already been studied and which issues still need to be investigated. Therefore, there is a need to conduct a systematic literature review to provide a comprehensive overview of SC resilience initiatives and strategies. For the review and synthesis conducted in this paper, 151 relevant articles were identified through a systematic search and selection of papers published between 2010 and 2021. First, the main themes of the SCRES strategies were categorized. The development of SCRES strategies for preparedness, response, and recovery, aimed at mitigating SC disruptions, was reviewed. Second, a detailed analysis of research developments in SCRES strategies was conducted, along with an investigation into the methodological, theoretical, and contextual justifications for tackling SC disruptions. Third, literature on SCRES strategies was synthesized for mapping and identifying potential research gaps. The analysis revealed that there is a scarcity of simulation model-based and theoretically grounded studies to mitigate large-scale SC disruptions. Moreover, it was also found that most studies have identified SCRES strategies for low-demand luxury products, while high-demand essential products and services have largely been ignored. Finally, based on the analysis, this article identifies research questions and future research directions for the field of SCRES research. These can guide academics and practitioners in designing and leading effective research in the field.